A semi-automatic method for indirect orientation of aerial images using ground control lines extracted from airborne laser scanner data - Dos Santos, Daniel Rodrigues; Tommaselli, Antonio Maria Garcia [UNESP]; Dalmolin, Quintino; Mitishita, Edson Aparecido (My University, 2012)
This paper presents a method for indirect orientation of aerial images using ground control lines extracted from airborne Laser system (ALS) data. This data integration strategy has shown good potential in the automation of photogrammetric tasks, including the indirect orientation of images. The most important characteristic of the proposed approach is that the exterior orientation parameters (EOP) of a single or multiple images can be automatically computed with a space resection procedure from data derived from different sensors. The suggested method works as follows. Firstly, the straight lines are automatically extracted in the digital aerial image (s) and in the intensity image derived from an ALS data-set (S). Then, correspondence between s and S is automatically determined. A line-based coplanarity model that establishes the relationship between straight lines in the object and in the image space is used to estimate the EOP with the iterated extended Kalman filtering (IEKF). Implementation and testing of the method have employed data from different sensors. Experiments were conducted to assess the proposed method and the results obtained showed that the estimation of the EOP is function of ALS positional accuracy.
Keywords: ALS data-set; Ground control lines; IEKF; Indirect orientation; Line-based coplanarity model; Aerial images; Airborne laser scanners; Airborne Laser Systems; Coplanarity; Data integration; Data sets; Extended Kalman filtering; Exterior orientation parameters; Ground control; Image space; Intensity images; Multiple image; Positional accuracy; Semiautomatic methods; Space resection; Degrees of freedom (mechanics); Rock mechanics; Sensors; Image processing